Interrupting Dissociation of Players through Real-Time Digital Tasks during Online Gambling - Ceyda Kiyak (16810665) (2023)
Online gambling is relatively easier to access compared to traditional one, so it can pose specific risks to individuals such as causing isolation, lack of interruption and dissociation. Intermittent interactions that require cognitive process can interrupt a task and capture the attentional focus which can help to break the dissociative state of players while playing. This study proposes an approach of using digital tasks to interrupt the dissociation of players during online gambling. We investigated the effectiveness of the approach through mixed methods where participants (N = 50) were invited to the computerised lab experiment and randomised to five conditions. Participants received digital tasks as an interruption while playing online slot gambling and their response time to the interruptions was measured. After the play, participants completed the Jacob’s Dissociation Questionnaire, and the Acceptability Questionnaire (both Likert scale and open-ended questions). The analysis revealed that there was a significant main effect of the interruptions in terms of response times, and a significant interaction between the interruptions and the digital tasks. Five main themes were generated after Thematic Analysis of the qualitative data: (1) Distraction, (2) Awareness, (3) User experience, (4) Considerations for design and (5) Considerations for technology. Digital tasks could be potentially useful tools to interrupt players’ dissociation during online gambling and support behavioural awareness and change towards more conscious and responsible gambling. Other Information Published in: International Journal of Human–Computer Interaction License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/10447318.2023.2233127